ANALISIS KUALITAS PELAYANAN KESEHATAN PADA PUSAT KESEHATAN MASYARAKAT (PUSKESMAS) PADANGSARI, BANYUMANIK, SEMARANG - Noviana Anjani Perwitasari; Nina Widowati; Susi Sulandari (Journal of Public Policy and Management Review, 2013)
Health center represent one of the public organization structure giving service in health area to common society that is Social Health Center. Health center is a health facility assigned to deal with the issue for public health in sub district. This study aims to find out and get a clear picture about the quality of services provided by Public Health Care of Padangsari. Type used is descriptive qualitative view of the five dimensions of service.the results showed of the five dimensions of health care quality assessment showed value unfavorable. It is evident from the results of the ynterviews show that the dimension. To inprove the quality of health care, public health centers should consider Padangsari service user satisfaction.